Electronic filter design handbook - Williams, Arthur Bernard (McGraw-Hill, 2006)
McGraw-Hill's classic Electronic Filter Design Handbook has now been completely revised and updated for a new generation of design engineers. Packed with more than 200 detailed illustrations, the Fourth Edition features: Expert coverage of the full range of filter designs as well as an introduction to microwave filters ; a CD with powerful Excel worksheets that perform calculations from just a few data inputs ; sophisticated guidelines for selecting state-of-the-art components ; and a wealth of helpful examples for all filter types with digital filter examples presented in MATLAB